Effect of the Rashba and Dresselhaus spin-splitting terms on the electron g factor in semiconductor quantum wells under applied magnetic fields - Bruno-Alfonso, A. [UNESP]; Porras-Montenegro, N.; Reyes-Gómez, E.; Oliveira, L. E. (Elsevier, 2008)
We use the Ogg-McCombe Hamiltonian together with the Dresselhaus and Rashba spin-splitting terms to find the g factor of conduction electrons in GaAs-(Ga,Al)As semiconductor quantum wells (QWS) (either symmetric or asymmetric) under a magnetic field applied along the growth direction. The combined effects of non-parabolicity, anisotropy and spin-splitting terms are taken into account. Theoretical results are given as functions of the QW width and compared with available experimental data and previous theoretical works. © 2007 Elsevier B.V. All rights reserved.
Keywords: Dresselhaus; Quantum well; Rashba; Spin-splitting; Anisotropy; Electrons; Magnetic fields; Dresselhaus spin-splitting; Electron g factor; Semiconductor quantum wells